Pengaruh Motivasi dan Kompensasi Terhadap Kinerja Guru Di SMKN Pertanian Kota Serang - Rosita Rosita; Mohamad Rifki Rosyadi; Rubiatul Hudaefah (Prosiding Amal Insani Foundation, 2023)
This study aims to analyze the performance of teachers at SMKN Pertanian Kota Serang. This study uses motivation and compensation variables to analyze the effect of teacher performance. The population in this study were all teachers at Serang City Agricultural Vocational School. This population amounted to 54 teachers. This study used the census method by giving questionnaires to the entire population of 54 teachers. Data collection was carried out using the questionnaire method, namely by providing a list of questions or questionnaires directly to the respondents. Data analysis techniques in this study used SEM (Structural Equation Model) analysis which was operated through the Smart PLS program. The results showed that the variables of motivation and compensation had a significant positive effect on teacher performance.